2021
DOI: 10.1007/s00127-021-02055-3
|View full text |Cite|
|
Sign up to set email alerts
|

Total and cause-specific mortality in patients with personality disorders: the association between comorbid severe mental illness and substance use disorders

Abstract: Purpose To investigate the mortality in both in- and outpatients with personality disorders (PD), and to explore the association between mortality and comorbid substance use disorder (SUD) or severe mental illness (SMI). Methods All residents admitted to Norwegian in- and outpatient specialist health care services during 2009–2015 with a PD diagnosis were included. Standardized mortality ratios (SMRs) with 95% confidence intervals (CI) were estimated in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Severe unipolar depression is associated with a life expectancy decrease of 10 to 14 years . Personality disorders, substance use disorders, anxiety disorders, and posttraumatic stress disorder are also associated with increased mortality. The substantial impact of psychiatric morbidity on physical health is multicausal, with key contributors believed to be an unhealthy lifestyle, insufficient somatic care, metabolic side effects of psychotropic medications, and biological factors associated with the psychiatric disorder (eg, chronic neurohormonal stress) .…”
Section: Introductionmentioning
confidence: 99%
“…Severe unipolar depression is associated with a life expectancy decrease of 10 to 14 years . Personality disorders, substance use disorders, anxiety disorders, and posttraumatic stress disorder are also associated with increased mortality. The substantial impact of psychiatric morbidity on physical health is multicausal, with key contributors believed to be an unhealthy lifestyle, insufficient somatic care, metabolic side effects of psychotropic medications, and biological factors associated with the psychiatric disorder (eg, chronic neurohormonal stress) .…”
Section: Introductionmentioning
confidence: 99%
“…There was no discernible trend to distinguish between studies which did or did not report a significant association. Four studies measured suicide death as an outcome, with three reporting a significant association with PD [ 30 , 32 , 34 , 41 ]. Only Sumlin et al (2020) reported no association between PD and suicide death; however, the sample size of this study was considerably smaller ( N = 162) than that of the other three studies (range: from 14,103 to 54,350 participants).…”
Section: Resultsmentioning
confidence: 99%
“…Education level, obtained from the Participation in Education Register [ 25 ], was used as a proxy for socioeconomic status [ 26 ]. The analyses were also adjusted for year of birth, age at their first personality disorder diagnosis, parity, somatic and psychiatric comorbidity, and inpatient care as a proxy for severity as this is associated with a higher mortality risk than outpatient care alone in patients with personality disorders [ 21 , 27 ] (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have focused on women given that they are three times more likely to be diagnosed with clinical BPD than men [ 17 ] despite a similar population prevalence in both sexes [ 20 ]. Women diagnosed with BPD also have a higher risk of death, especially for unnatural causes of death [ 17 , 21 ]. Research shows that women with ADHD and BPD share more clinical features than men [ 14 ].…”
Section: Introductionmentioning
confidence: 99%